Timing: ls That All There ls? - Maher, Robert (The International Journal of Accounting and Business Society, 1996)
Accounting standard setters in North America, and around the world have promulgated numerous pronouncements on ï¬nancial reponing. I would like to suggest that all of the diverse issues covered by these pronouncements are directly related. They all arise from timing, The problem that is central to accrual accounting. Appropriate recognition of this fact might make the study and practice of accounting much simpler than is currently the case.